The Methodology of Directing Readings in the Book "Taqrib al-Ma'ani" A Descriptive and Analytical Study of the Verses in Surat al-Baqarah (Sirte University Journal of Humanities, 2025)
This research aims to elucidate the linguistic methodology employed in the book Taqrib al-Ma'ani fi Sharh Hirz al-Amani by Sayyid Lashin Abu al-Farah and Khalid bin Mohammed al-Ilmi. This is achieved through an applied study of the passages dedicated to directing the Quranic readings (Qira'at) within Surah Al-Baqarah. The study employs a descriptive-analytical methodology by extracting all relevant passages from the book, then classifying and analyzing them to uncover the principles upon which the authors based their explanations. The findings indicate that the authors relied primarily on linguistic reasoning at the syntactic (I'rab), morphological, and phonological levels. Their approach is characterized by conciseness and focus, staying true to the book's title, "Approximating the Meanings," which aims for simplification and facilitation. The analysis also revealed the book's emphasis on the semantic integration of the different readings, demonstrating how each reading offers a complementary dimension that enriches the text without contradiction. The study concludes that Taqrib al-Ma'ani presents a clear methodological model for simplifying the science of directing the Qira'at for contemporary learners.
Keywords: Quranic Readings; Qira'at; Directing Readings; Tawjih al-Qira'at; Taqrib al-Ma'ani; Surah Al-Baqarah; Linguistic Methodology; Syntactic and Morphological Reasoning